Rancang Bangun Perangkat Lunak Pengelolaan Data Mortalitas Pasien Rawat Inap - Nurhayati; Khoirul Mustofa; Istiqomah Novitasari (Universitas Duta Bangsa Surakarta, 2022)
Mortality data is one of the output information generated from the medical record unit. Mortality data includes information on inpatient mortality data which includes inpatient mortality data reports, inpatient mortality index reports, certificates of cause of death. PKU Muhammadiyah Kartasura Hospital has problems in managing mortality data, including recording inpatient mortality data which is still manual so that it is difficult to produce mortality data reports. This study aims to produce inpatient mortality data management software. The research method includes descriptive research with a system development life cycle approach. The software was developed using a website with a mysql database. This study is able to produce information on inpatient mortality data which includes inpatient mortality data reports, inpatient mortality index reports, certificates of cause of death. The result is that medical record officers are helped by the existence of mortality data management software